2022
DOI: 10.3390/antiox11071313
|View full text |Cite
|
Sign up to set email alerts
|

Mangifera indica L. Leaves as a Potential Food Source of Phenolic Compounds with Biological Activity

Abstract: It is well recognized that functional foods rich in antioxidants and antiinflammation agents including polyphenols, probiotics/prebiotics, and bioactive compounds have been found to have positive effects on the aging process. In particular, fruits play an important role in regular diet, promoting good health and longevity. In this study, we investigated on biological properties of extract obtained from Mangifera indica L. leaves in preclinical in vitro models. Specifically, the profile and content of bioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…With the only exception of the highest concentration for both treatments (>80 μL/mL), no toxicity compared to the control was observed for all formulations ( Figure 6 ). The data confirm that nanostructured lipid carriers at the same concentrations as those of mangiferin used in previous studies show no cytotoxicity effects alone or loaded with MGN [ 9 , 29 , 38 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…With the only exception of the highest concentration for both treatments (>80 μL/mL), no toxicity compared to the control was observed for all formulations ( Figure 6 ). The data confirm that nanostructured lipid carriers at the same concentrations as those of mangiferin used in previous studies show no cytotoxicity effects alone or loaded with MGN [ 9 , 29 , 38 ].…”
Section: Resultssupporting
confidence: 88%
“…The antioxidant properties of polyphenols or natural substances are often related to a decrease in ROS formation in the tested cells. The presence of ROS reflects the induction of oxidative stress and is responsible for the onset of cardiovascular, metabolic and neoplastic diseases, as well as macular degeneration [ 9 , 28 , 39 , 40 , 41 ]. To investigate a possible maintenance of the protective role of MGN in oxidative stress, we treated ARPE-19 in the presence and absence of 0.5 mM H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DPPH free radical scavenging activity of cookies was determined according to the method reported by Sferrazzo et al [ 26 ] with some modifications. DPPH solution (900 μL) was added to 100 μL cookie extracts and the mixture reacted for 10 min in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Mango fruit is appreciated for its nutritive and nutraceutical properties [ 32 , 33 ]. It has been shown that different parts of the plant and of the fruit exert anti-inflammatory, anti-oxidant and anti-tumor effects in in vitro as well as in vivo models because of the presence of a wide range of polyphenols [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%